H. Rider Haggard's "Nada the Lily": A Triumph of Translation. - Monsman, Gerald (English Literature in Transition, 1880-1920, 2004)
This article discusses the book "Nada the Lily," by H. Rider Haggard. This book is described as a romance or a tale that implies poetic feelings and strange or even legendary happenings. Early missionaries and British functionaries called these happenings "dark superstitions". The writer that most influenced Haggard was nineteenth century E. B. Taylor and his book "Primitive Culture."